The effect of office environment towards employees’ job productivity among employee at SME CORP. Malaysia / Ahmad Suhaimi Johari - Johari, Ahmad Suhaimi (2014)
Training program is very important and take serious concern by human resource and top management in every business field from small and midsize business to global organization, including private and government sector. Many employers believe that training program is very important because it may lead to the low absenteeism, enhance the productivity, as well as motivation for the employee job performance. The environment of the office will affect the motivation and also the productivity of the organization. Surrounding will help the performance of the employee to maintain their performance. To examine the study a literature review has been done on different aspects of environment. The findings of this study suggest many factors which affect training effectiveness such as Work environment (light, office spatial, and noise) will give the performance to the employee.